Collaborative Learning Integrated Pancasila Profile Based on Cultural Diversity to Improve Critical Thinking Ability - Risky Putri Yani; Feri Tirtoni (STAI Hubbulwathan Duri, 2024)
Critical thinking is the ability to analyze, interpret and evaluate information objectively and rationally needed in the 21st century to face future challenges through innovative approaches in order to take advantage of opportunities in the digital and global era. Critical thinking skills at the elementary school level are still low and need to be improved through collaborative learning according to the implementation of the independent curriculum. The profile of Pancasila students is the skills that Indonesian students must have based on the noble values of Pancasila. This study aims to test the application of collaborative learning integrated with the Pancasila student profile based on cultural diversity with the Project Based Learning learning method to improve critical thinking skills. This study uses quantitative research pre-experiment method of one group pretest-posttest design. The subjects of this study involved 18 grade 4 students who were divided into small groups and calculated using the N-Gain test. The N-Gain test is a measuring technique to determine the effectiveness of a treatment before and after learning. The results of this study found the overall average N-Gain results showed moderate criteria between 0.3≤g≤0.7 and quite effective at a percentage between 56-75. Another result of this study, by doing collaborative learning students can become peer tutors and innovate to complete projects given by teachers from the development of an independent curriculum integrated with the Pancasila learner profile. Therefore, collaborative learning integrated with the Pancasila learner profile is concluded to improve critical thinking skills.